Screening for Potential Active Components of Fangji Huangqi Tang on the Treatment of Nephrotic Syndrome by Using Integrated Metabolomics Based on “Correlations Between Chemical and Metabolic Profiles” - Liu, Xiao; Zhou, Qi-Gang; Zhu, Xiao-Chai; Xie, Li; Cai, Bao-Chang (Frontiers in Pharmacology, 2019)
As far as the traditional Chinese medicine (TCM) prescription was concerned, what puzzled researchers most was how to select proper chemical markers to represent the whole pharmacological action system. In this paper, an integrated metabolomic method was presented for a systematic discovery of potential active components of Fangji Huangqi Tang (FHT), a well-known TCM prescription for nephrotic syndrome treatment, based on "correlations between chemical and metabolic profiles". Firstly, metabolomics study was carried out to select representative biomarkers of nephrotic syndrome. Then, after drug administration, the dynamic process of serum composition was investigated by UHPLC-ESI-Q-TOF-MS technique to detect the prototype and related metabolites of relative components from FHT. Pearson correlation analysis was finally used to find out the correlations between the endogenous metabolic spectrums and the chemical serum spectrums. As a result, 17 biomarkers for nephrotic syndrome indication were identified, and the main metabolic pathways of their concern included linoleic acid metabolism, cayanoamino acid metabolism, alpha-linolenic acid metabolism, glycine, serine and threonine metabolism, arachidonic acid metabolism and glycerophospholipid metabolism. Meanwhile, active components in FHT for nephrotic syndrome treatment were screened out, including (+)-tetandrine-demethylation, fefangjine hydrogenation, tetrandrine, N-methyfangchinoline, tetrandrine-demethylation, fangchinoline, glycyrrhetic acid, astragaloside II-alcoholde hydration, atractylenolide III-demethylation+hydrogenation, atractylenolide III-demethylation+hydrogenation and licoricone-N-acetylcysteine conjugation. Also, this study demonstrated a promising way to elucidate the compatibility effects of TCM prescription.